The notebook - Saramago, José (Verso, 2010)
"Provocative and lyrical, ... on the eve of the 2008 US presidential election, the author started jotting down his reflections on the world in which he lives. He evokes life in his beloved city of Lisbon, conversations with friends, and meditations on his favourite authors, often rendered with pointillist detail: precise observations on stories and moments of arresting significance that together comprise an acute view of our times. Characteristically critical and uncompromising, Saramago dissects the financial crisis, deplores Israels bombardment of Gaza, traces the ongoing inquiry into the execution of the Brazilian Jean Charles de Menezes on the London Underground, and charts the transition from the era of George W. Bush to that of Barack Obama." -- Book jacket.